Language in Complexity The Emerging Meaning - La Mantia, Francesco; Licata, Ignazio; Perconti, Pietro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This contributed volume explores the achievements gained and the remaining puzzling questions by applying dynamical systems theory to the linguistic inquiry. In particular, the book is divided into three parts, each one addressing one of the following topics: 1) Facing complexity in the right way: mathematics and complexity 2) Complexity and theory of language 3) From empirical observation to formal models: investigation of specific linguistic phenomena, like enunciation, deixis, or the meaning of the metaphorical phrases The application of complexity theory to describe cognitive phenomena is a recent and very promising trend in cognitive science. At the time when dynamical approaches triggered a paradigm shift in cognitive science some decade ago, the major topic of research were the challenges imposed by classical computational approaches dealing with the explanation of cognitive phenomena like consciousness, decision making and language. The target audience primarily comprises researchers and experts in the field but the book may also be beneficial for graduate and post-graduate students who want to enter the field.
Introduction.-The Game of Complexity and Linguistic Theorization -- Continuity in the Interactions between Linguistic Units -- Modeling Language Change -- The Case for Cognitive Plausibility -- System and Structure -- Hjelmslev and the Stratification of Signs and Language -- From Topology to Quasi-Topology -- Fiat Lux versus Fiat Lumen -- Two Ways into Complexity -- Language and Brain Complexity.
Keywords: Dynamics; Nonlinear theories; Computational linguistics; Natural language processing (Computer science).; Neural networks (Computer science) .; Neurosciences; Applied Dynamical Systems; Computational Linguistics; Natural Language Processing (NLP).; Mathematical Models of Cognitive Processes and Neural Networks; Neuroscience